Feeding of partially hydrogenated fish oils to rats in comparison with partially hydrogenated soybean oil and refined rapeseed oil. A combined chronic oral toxicity and carcinogenicity study with in utero phase - Duthie, I.F; Barlow, S.M; Ashby, R; Tesh, J.M; Whitney, J.C; Saunders, A; Chapman, E; Norum, K.R; Svaar, H; Opstvedt, J (Acta medica Scandinavica, supplementum, 1988)
Partially hydrogenated fish oils (PHFO) have been widely used in human food products for many years, particularly in Europe, North and South America and in South Africa. Animal studies, mainly with rapeseed oil, suggested that erucic acid might be responsible for morphological changes in the myocardium. It was suggested that other members of the docosenoic (22:1) family of fatty acids might produce similar effects to those ascribed to erucic acid. Certain PHFO can contain relatively high levels of these other isomers. Thus it was decided to evaluate PHFO of differing 22:1 levels in comparison with partially hydrogenated soybean oil (PHSBO) and refined rapeseed oil (LEAR) in a rat life span study, preceded by a breeding period in which the experimental lipids were fed to male and female parents. Two commercially produced PHFO were selected to represent the lower (PHFO-L) and upper (PHFO-U) range of 22:1 contents, 4.3 and 13.8%, respectively. A third test oil was prepared from a 50:50 blend of these (PHFO-M) to provide and intermediary 22:1 level. The control PHSBO and LEAR contained 0 and 1.0% 22:1, respectively. These experimental oils were included in semi-purified diets at 8 and 16%, respectively, in the breeding and life span periods of the study, together with 4% of oil mixtures providing essential fatty acids (EFA). Specific pathogen free (SPF). Wistar weanling rats, 200 of each sex, provided the subjects for the breeding period. Sufficient numbers of offspring were obtained in suitable condition from each treatment group to allow selection of a total of 555 weanlings for allocation to the five dietary treatments of the life span period of the study. For the life span period of the study, which was terminated after 107 to 110 weeks of treatment, 50 subjects were allocated to each of the PHSBO, PHFO-L and PHFO-U dietary groups, and 50 males to each of the LEAR and PHFO-M groups. The remaining subjects were allocated to sub-groups for sacrifice four days or 26 weeks after introduction of the life span period diets. All life span group subjects were weighed and had their food intakes recorded, and were subjected to clinical examination, routinely. At designated stages, ophthalmoscopic examination of all subjects was carried out, and samples of blood and urine were obtained from sub-groups for laboratory analysis. All decedent and terminated life span group subjects were subjected to post mortem examination, with weighing of 16 organs.